Search 73,830 tutors
FIND TUTORS
Ask a question
1 0

Whats -6(4-3x)-5x= ?x + ?

Tutors, please sign in to answer this question.

2 Answers

The "-6" is multiplied (distributed) across the parentheses:  -6 * 4 and -6 * -3x, which is then -6 * 4 = -24 and -6 * -3x, which is then 18x.
 
Now you have -24 + 18x - 5x = x
 
Combine the x's.  We need to subtract an "x" from both sides of the equation.  This keeps the equation in balance.
 
-24 + 18x - 5x - x = x - x becomes -24 + 13x - x = 0 which becomes -24 + 12x = 0
 
Now, we solve for "x", subtracting "12x" from both sides of the equation.  This keeps the equations in balance, again.
 
-24 +12x -12x = 0 - 12x become -24 = -12x.
 
Divide both sides by -12:
 
2 = x or
 
x = 2
 
Cross check
-6(4 - 3x) - 5x = x
-6(4 - 3(2)) - 5(2) = 2
-6(4 - 6) - 10 = 2
-6(-2) - 10 = 2
12 - 10 = 2
 
Got it...
 
Good luck
 
Bob